Vida cotidiana, afetividade e esquizofrenia: Um estudo em adultos portugueses - Freire, Teresa (2014)
This study aimed to analyse the daily life experiences of Portuguese people with schizophrenia diagnosed with particular emphasis on the affective dimension of experience. The Experience Sampling Method (ESM) was used to collect data on the daily life experience, over a week. Participated in this study 14 people diagnosed with schizophrenia for at least three years, medically stabilized, living in the community and professional rehabilitation targets. The results indicate that the participants spend most of their time in their homes, alone or with their families and performing leisure activities. The positive affective aspects (feeling and emotions) predominate in their daily lives. However this situation changes when individuals are alone, with a sharp decrease in the positive affectivity and a significant increase in the negative one. These results reinforce the perspective of the community integration and the need for this to be accompanied by the creation of community structures that promote integrated rehabilitation activities, structured and promoters of the development and the social interactions.